Effect of non-uniform rebar corrosion on structural performance of RC structures: A numerical and experimental investigation. (10th January 2020) - Biswas, Rajib Kumar; Iwanami, Mitsuyasu; Chijiwa, Nobuhiro; Uno, Kunihiko
Highlights: A 3D non-linear finite element model for non-uniformly corroded RC beams was developed. Effect of non-uniform rebar corrosion on the structural performance of RC beams was investigated by the experimental program. Global behavior of RC structures subjected to non-uniform rebar corrosion was studied. Abstract: The structural behavior of reinforced concrete (RC) beams subjected to non-uniform rebar corrosion is studied here by developing a simplified numerical approach using three-dimensional (3D) nonlinear finite element (FE) analysis and experimental study. In order to validate the proposed numerical model and to understand the influence of nonuniform rebar corrosion on the structural performance of RC beams, seven reinforced concrete beams with identical dimensions and reinforcement layout were tested under static loading. Out of the seven beams, six beams were subjected to a different level of corrosion using an electrochemical method, and another beam was used as a control specimen without corrosion. To further verify the accuracy of the numerical model, another experimental study from the literature was selected. Finally, to investigate the influence of non-uniform rebar corrosion on the global behavior of RC structures, a hypothetical building was modelled based on the experimental result, and non-linear structural analysis was carried out. Results from the experimental and numerical study demonstrated that non-uniform corrosion of steel bars led to a significant decrease in the ductility and load carrying capacity of the RC beams. Findings of this study will be useful in assessing the residual structural performance of the RC structures with non-uniform rebar corrosion. Therefore, this study will facilitate the optimization of the maintenance and repair strategies for the deteriorated RC structures.